Melatonin induces nitric oxide and the potential mechanisms relate to innate immunity against bacterial pathogen infection in Arabidopsis. Issue 1 (26th May 2015) - Shi, Haitao; Chen, Yinhua; Tan, Dun‐Xian; Reiter, Russel J.; Chan, Zhulong; He, Chaozu
Abstract Melatonin (N‐acetyl‐5‐methoxytryptamine) is a naturally occurring small molecule, serving as important secondary messenger in the response of plants to various biotic and abiotic stresses. However, the interactions between melatonin and other important molecules in the plant stress response, especially in plant immunity, are largely unknown. In this study, we found that both melatonin and nitric oxide (NO) levels in Arabidopsis leaves were significantly induced by bacterial pathogen (Pst DC3000) infection. The elevated NO production was caused by melatonin as melatonin application enhanced endogenous NO level with great efficacy. Moreover, both melatonin and NO conferred improved disease resistance against Pseudomonas syringe pv. tomato (Pst) DC3000 infection in Arabidopsis. NO scavenger significantly suppressed the rise of NO which was induced by exogenous application of melatonin. As a result, the beneficial effects of melatonin on the expression of salicylic acid (SA)‐related genes and disease resistance against bacterial pathogen infection were jeopardized by use of a NO scavenger. Consistently, melatonin application significantly lost its effect on the innate immunity against P. syringe pv. tomato (Pst) DC3000 infection in NO‐deficient mutants of Arabidopsis. The results indicate that melatonin‐induced NO production is responsible for innate immunity response of Arabidopsis against Pst DC3000 infection.